Pengaruh kadar haemoglobin dan hematokrit dengan insiden kegagalan arteriovenous fistula pada pasien gagal ginjal kronik stadium V - Satrio Ryandi; Ketut Putu Yasa; I Gede Raka Widiana (Intisari Sains Medis, 2020)
Chronic Kidney Disease (CKD) is a disease that requires important attention. Chronic kidney failure is mentioned as kidney damage that occurs more or equal to 3 months in the form of abnormal structural or functional damage from the kidney with or without a decrease in GFR. Management of chronic renal failure is hemodialysis. Hemodialysis performed on patients with chronic renal failure requires appropriate vascular access.Method: This study involved 76 respondents with a cross-sectional observation design in patients with stage V chronic kidney disease in Sanglah Hospital Denpasar from January 2018 to December 2018 conducted by arteriovenous fistula, with an age range of 17 years to 65 years, who have undergone regular hemodialysis for more than 3 month and with complete medical records.Result: From this study it was found, characteristics based on age ? 55 years were 40 respondents (52.6%) and age <55 were 36 respondents (47.4%). Characteristics based on gender obtained male data as many as 43 respondents (56.6%) and women as many as 33 respondents (43.4%). Characteristics based on BMI obtained a median value of 26. Characteristics based on BMI ? 26 Kg / m2 were 39 respondents (51.3%) and BMI <26 Kg / m2 were 37 respondents (48.7%). Characteristics based on INR ? 1.2 were 10 respondents (13.2%) and INR 0.9-1.1 were 66 respondents (86.8%). Characteristics based on DM disease obtained with DM disease data as many as 17 respondents (22.4%) and without DM disease as many as 59 respondents (77.6%). Patients with hemoglobin hemoglobin levels <9.9 gr / dl with non-patent AVF 47 (73.4%) and ? 9.9 gr / dl with non-patent AVF 17 (26.6%) while hemoglobin levels <9, 9 gr / dl with patent AVF of 3 (25%) and ? 9.9 gr / dl with patent AVF of 9 (75%) [PR=1,4; IK1,07-1,91; p=0,001].Conclusion: Hemoglobin <9.9 associated with failure of AVF. Low hemoglobin is the most important risk factor for the occurrence of AVF failure in CRF patients. Hematocrit <29.18 related to AVF failure. Gagal Ginjal Kronik (GGK) merupakan penyakit yang memerlukan perhatian penting. Gagal ginjal kronik disebutkan sebagai kerusakan ginjal yang terjadi lebih atau sama dengan 3 bulan baik berupa kerusakan struktur atau fungsi yang abnormal dari ginjal dengan atau tanpa penurunan GFR yang dilakukan kepada pasien GGK memerlukan akses vaskular yang tepat.Metode: Penelitian ini melibatkan 76 responden dengan rancangan observasi crossectional pada pasien  gagal ginjal kronis stadium V di RSUP Sanglah Denpasar dari mulai bulan Januari 2018 sampai Desember 2018 yang dilakukan arteriovenous fistula, dengan rentang umur 17 tahun sampai 65 tahun, yang sudah menjalani hemodialisis regular lebih dari 3 bulan dan dengan catatan medis yang lengkap. Hasil: Karakteristik berdasarkan umur ? 55 tahun sebanyak 40 responden (52,6%) dan umur < 55 sebanyak 36 responden (47,4%). Karakteristik berdasarkan jenis kelamin didapatkan data laki-laki sebanyak 43 responden (56,6%) dan perempuan sebanyak 33 responden (43,4%). Karakteristik berdasarkan BMI didapatkan nilai median 26. Karakteristik berdasarkan BMI  ? 26 Kg/m2 sebanyak 39 responden (51,3%) dan BMI < 26 Kg/m2 sebanyak 37 responden (48,7%). Karakteristik berdasarkan INR  ? 1,2 sebanyak 10 responden (13,2%) dan INR 0,9-1,1 sebanyak 66 responden (86,8%). Karakteristik berdasarkan penyakit DM didapatkan data dengan penyakit DM sebanyak 17 responden (22,4%) dan tanpa penyakit DM sebanyak 59 responden (77,6%).  Pasien dengan kadar haemoglobin Haemoglobin < 9,9 gr/dl dengan AVF tidak paten sebanyak 47(73,4%) dan  ? 9,9 gr/dl dengan AVF tidak paten sebanyak 17(26,6%) sedangkan kadar haemoglobin < 9,9 gr/dl dengan AVF  paten sebanyak 3 (25%)  dan  ? 9,9 gr/dl dengan AVF  paten sebanyak 9 (75%) [PR=1,4; IK1,07-1,91; p=0,001].Simpulan: Hemoglobin < 9,9 berhubungan dengan kegagalan AVF. Haemoglobin yang rendah menjadi faktor risiko yang paling berperan terhadap terjadinya kegagalan AVF pada pasien GGK..Hematokrit < 29,18 berhubungan dengan kegagalan AVF.